Supply curves for yields of dairy products from first-lactation Holstein Friesian, Jersey and Holstein Friesian-Jersey crossbred cows accounting for seasonality of milk composition and production - Sneddon, NW; Lopez-Villalobos, N; Davis, SR; Hickson, RE; Shalloo, L; Garrick, DJ (New Zealand Society of Animal Production (INC), 2016)
The economic efficiency of a milk-processing system is influenced by seasonality of the milk supply, and changes to milk composition, influences the product potential of that milk. Lactation curves for milk yield and composition for seasonal calving first-lactation Holstein Friesian (F), Jersey (J) and Holstein Friesian-Jersey crossbred (FxJ) cows were used as inputs in a deterministic simulation model to produce seasonal curves for daily yields of dairy products. The dairy products were whole milk powder, skim milk powder, cheese, or butter. Dairy product potential was estimated for each animal from a population of 4333 mixed-breed, first-lactation cows. Lactation lengths differed (P<0.0001), among F, FxJ, and J, which averaged 219, 222 and 221 days respectively. Total-lactation milk yield was different (P<0.0001) among breeds and averaged 3257, 3092 and 2902 litres for F, FxJ and J cows, respectively. Whole-milk powder potential (yield per 1000 L of milk) was greatest at the start of the season and least at the end of the season, whereas cheese-production potential (yield per 1000 L of milk) followed the opposite pattern. Total-lactation whole-milk powder yield was different among breeds (P<0.0001) at 366, 338 and 312 kg of whole-milk powder for F, FxJ and J cows, respectively. Total-lactation cheese yield was also different among breeds (P<0.0001), and was 371, 375 and 361 kg for F, FxJ and J cows, respectively. The supply curves indicate that milk is best processed into whole or skim milk powder during peak season, and cheese and butter at the end of lactation. However, seasonal production of specific products would limit the use of by-product lactose from cheese manufacture in the production of milk powders, and thus negate the efficiency gains from changes to processing priorities.
Keywords: Lactation curves; New Zealand; Dairy Cattle; Dairy production; Lactose; 0702 Animal Production